Architectural identities : domesticity, literature and the Victorian middle classes - Tange, Andrea Kaston, 1970- (University of Toronto Press, 2010)
Architectural Identities links Victorian constructions of middle-class identity with domestic architecture. In close readings of a wide range of texts, including fiction, autobiography, housekeeping manuals, architectural guides and floor plans, Andrea Kaston Tange argues that the tensions at the root of middle-class self-definition were built into the very homes that people occupied. Individual chapters examine the essential identities associated with particular domestic spaces, such as the dining room and masculinity, the drawing room and femininity, and the nursery and childhood. Autobiographical materials by Frances Hodgson Burnett, Thomas and Jane Welsh Carlyle, Elizabeth Gaskell, and Linley and Marion Sambourne offer useful counterpoints to the evidence assembled from fiction, demonstrating how and where members of the middle classes remodelled the boundaries of social categories to suit their particular needs. Including analyses of both canonical and lesser-known Victorian authors, Architectural Identities connects the physical construction of the home with the symbolic construction of middle-class identities.